2022
DOI: 10.1017/lap.2021.54
|View full text |Cite
|
Sign up to set email alerts
|

Negative Partisanship in Latin America

Abstract: The literature on comparative partisanship has demonstrated the low rates of party identification in Latin America. Such low rates are commonly interpreted as a sign of citizens’ disengagement with parties and democracy in the region. This article revisits this interpretation by considering voters’ adverse affection toward a party, or negative partisanship. It shows that examining the negative side of partisanship can help us develop a clearer perspective on the partisan linkages in the electorate. To support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…The results of this research note illustrate the increasing importance of out-party animus among Latin American voters (Haime and Cantú, 2022; Melendez and Rovira Kaltwasser, 2019), even structuring party systems in the region (e.g., Brazil, Samuels and Zucco, 2018). In Mexico's 2018 presidential election, the vote for López Obrador is strongly associated with affective polarization and the perception that the PRI and PAN represented the same political alternative.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The results of this research note illustrate the increasing importance of out-party animus among Latin American voters (Haime and Cantú, 2022; Melendez and Rovira Kaltwasser, 2019), even structuring party systems in the region (e.g., Brazil, Samuels and Zucco, 2018). In Mexico's 2018 presidential election, the vote for López Obrador is strongly associated with affective polarization and the perception that the PRI and PAN represented the same political alternative.…”
mentioning
confidence: 67%
“…In fact, animus toward the Democratic-leaning social groups strongly predicted support for Trump's candidacy (Mason et al, 2021), which was activated by his racist comments during the campaign. In Latin America, the out-party animus increasingly affects social dissimilarity (Haime and Cantú, 2022), political identification (Meléndez and Rovira Kaltwasser, 2019), and even structures party systems (Samuels and Zucco, 2018;Meléndez, 2022). In Brazil, Bolsonaro's victory was rooted in strong anti-petismo sentiment (anti-Worker's Party feeling, Samuels and Zucco, 2018) as well as a strong disenchantment with political institutions amid corruption scandals involving major parties.…”
mentioning
confidence: 99%
“…This line of explanation should go well beyond Brazil. Negative partisanship is particularly important for understanding political attitudes in Eastern Europe (Rose and Mishler 1998 ) and several Latin American countries (Haime and Cantú 2022 ), contexts in which positive identification with parties is low and political competition is often dichotomized. Further, the rise of negative partisanship in Western Europe (Meléndez and Kaltwasser 2021 ) and the United States (Abramowitz and Webster 2016 ) suggests negative partisanship can exert independent effects on political behaviour even in more established, high-partisan polities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The strength of negative political identities amongst the Brazilian electorate bespeaks an increasingly hostile and uncompromising polity, which should worry political practitioners and scientists. As citizens turn away from parties (Dalton and Wattenberg 2002 ), negative political identities are an increasingly important factor structuring political competition both in new (Haime and Cantú 2022 ) and advanced democracies alike (Bankert 2021 ). The theoretical and empirical contributions on the concept presented by this paper should thus be of significant relevance to the study of comparative political behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have previously argued that partisanship in Mexico is weak (Greene 2011), recent studies in Mexico (Castro Cornejo 2021) and across Latin America (Lupu 2015;Calvo and Ventura 2021;Haime and Cantú 2022) have found that, similar to old democracies, partisans are more informed and engaged than nonpartisans and that their partisan attachments moderate their attitudes and voting behavior. In that sense, this research argues that citizens in young democracies like Mexico also engage in partisanmotivated reasoning (Taber and Lodge 2006)-that is, the tendency to accept information with the goal of arriving at predetermined conclusions.…”
Section: Introductionmentioning
confidence: 99%